2023
DOI: 10.1037/hea0001256
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccination hesitancy in adults in the United Kingdom: Barriers and facilitators to uptake.

Abstract: Objective: Immunization is a primary method for addressing COVID-19. Uptake in high-risk groups has been strong, however, vaccination hesitancy is more prominent among younger adults. This research sought to identify the factors influencing vaccine uptake in 18–55-year-olds. Method: Study 1, a qualitative survey (n = 80), identified beliefs about COVID vaccines and immunization programs. Study 2 (n = 473) tested whether the factors identified in study 1 predicted intention for self-vaccination and parental int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The other 11 papers in this special issue present novel research findings across a wide range of aspects of health psychology and vaccination practice. Most of them focus exclusively on COVID-19 (Bogg et al, 2023; Buscemi et al, 2023; Delporte et al, 2023; Eberhardt and Ling, 2023; Husted et al, 2023; Ku et al, 2023; Martin et al, 2023; Preis et al, 2023; Warren et al, 2023), but others concern influenza (Bender et al, 2023; Brumbaugh et al, 2023) and HPV vaccines (Brumbaugh et al, 2023). Six of the research articles (Bogg et al, 2023; Brumbaugh et al, 2023; Buscemi et al, 2023; Martin et al, 2023; Preis et al, 2023; Warren et al, 2023) report on studies conducted in the United States, while two (Eberhardt and Ling, 2023; Husted et al, 2023) were conducted in the United Kingdom, one (Bender et al, 2023) in Germany, one (Delporte et al, 2023) in Belgium, and one (Ku et al, 2023) in South Korea.…”
Section: Overview Of the Special Issuementioning
confidence: 99%
See 2 more Smart Citations
“…The other 11 papers in this special issue present novel research findings across a wide range of aspects of health psychology and vaccination practice. Most of them focus exclusively on COVID-19 (Bogg et al, 2023; Buscemi et al, 2023; Delporte et al, 2023; Eberhardt and Ling, 2023; Husted et al, 2023; Ku et al, 2023; Martin et al, 2023; Preis et al, 2023; Warren et al, 2023), but others concern influenza (Bender et al, 2023; Brumbaugh et al, 2023) and HPV vaccines (Brumbaugh et al, 2023). Six of the research articles (Bogg et al, 2023; Brumbaugh et al, 2023; Buscemi et al, 2023; Martin et al, 2023; Preis et al, 2023; Warren et al, 2023) report on studies conducted in the United States, while two (Eberhardt and Ling, 2023; Husted et al, 2023) were conducted in the United Kingdom, one (Bender et al, 2023) in Germany, one (Delporte et al, 2023) in Belgium, and one (Ku et al, 2023) in South Korea.…”
Section: Overview Of the Special Issuementioning
confidence: 99%
“…Two U.K.-based studies (Eberhardt and Ling, 2023; Husted et al, 2023) assessed a broad range of barriers and facilitators to COVID-19 vaccine intention and uptake. Eberhardt and Ling (2023) focused on constructs from the Protection Motivation Theory (PMT), especially conspiracy theory beliefs, in their research.…”
Section: Overview Of the Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…The HBM has also been used to identify key drivers of the intention to vaccinate against seasonal Influenza (Chen et al, 2011;Fall et al, 2018), HPV (Donadiki et al, 2014;Gerend & Shepherd, 2012), H1N1 Influenza (Fabry et al, 2011;Yang, 2015) and COVID-19 (Ellithorpe et al, 2022;Guidry et al, 2021;Husted et al, 2023;Shmueli, 2021;Wong et al, 2021;Zampetakis & Melas, 2021), but has yet to be applied to the intention to vaccinate against LD.…”
Section: Introductionmentioning
confidence: 99%
“…(2016) found that awareness and knowledge about the disease, the benefits of preventative behaviour and confidence in the ability to perform preventative behaviours ultimately improved precautionary behaviour. The HBM has also been used to identify key drivers of the intention to vaccinate against seasonal Influenza (Chen et al., 2011; Fall et al., 2018), HPV (Donadiki et al., 2014; Gerend & Shepherd, 2012), H1N1 Influenza (Fabry et al., 2011; Yang, 2015) and COVID‐19 (Ellithorpe et al., 2022; Guidry et al., 2021; Husted et al., 2023; Shmueli, 2021; Wong et al., 2021; Zampetakis & Melas, 2021), but has yet to be applied to the intention to vaccinate against LD.…”
Section: Introductionmentioning
confidence: 99%